Um modelo matemático multi terminais e uma metaheurística Adaptive Large Neighborhood Search para o problema de roteamento de navios aliviadores visando o escoamento de petróleo offshore - Basilio, Pedro da Matta e Andrade (2017)
The oil and natural gas production chain presents a large complexity and involves a set of steps to obtain such derivative. Particularly noteworthy are the logistics support services to production that must provide quick responses to the production system chain, minimizing costs. The importance of Floating Production Storage Offloading (FPSO), generally large vessels capable of producing, processing and storing the oil that is transferred to the land by shuttle tanks or by oil pipelines, is emphasized. In this context, the flow of oil by shuttle tanks, together with the effective establishment of the routes, is very relevant. Therefore, this work presents a mult-terminals mathematical model for the problem of shuttle tanks routing and an Adaptive Large Neighborhood Search meta - heuristic (ALNS) that is able to define shuttle tanks routes at a minimum cost. The computational tests showed that the mathematical model performs better than another proposed model in the literature and that the ALNS meta-heuristic is able to find good solutions in a reduced time.